Thomas Kuhn dan Teori Hubungan Internasional: Realisme sebagai Paradigma - Azwar Asrudin (Institute of International Studies, 2014)
This writing is the writer’s objections against Peter Van Ness’ claim on realist paradigm. In reference to Thomas Kuhn’s paradigm shift, Van Ness argued that realism, as what Kuhn would call “normal science” in international relations theory, is in a crisis because of its inability to explain some anomalies. According to Van Ness, rampant number of states doing security cooperation is enough to call realism is in a crisis as a paradigm. Through several cases on international anarchy, the writer argues that realism is still relevant and worthy to be called a paradigm in Kuhnian category.